Strategi Pengembangan Badan Usaha Milik Desa (BUMDes) Matansala Untuk Meningkatkan Pendapatan Asli Desa di Desa Matansala Kecamatan Bungku Tengah Kabupaten Morowali - Faudzan, Ahmad; Alimuddin, Nurwahidah; Sammintang, Samintang (Journal of Islamic Community and Development, 2026)
Village development is an important part of national development that aims to create an independent, prosperous, and sustainable society. With the existence of village development efforts in an area, the economy of the wider community will be achieved. This is due to the strong contribution of the rural economy, which has an impact on the welfare of the wider community. Research Objectives To determine and reveal strategies in increasing the original income of Matansala Village. To determine the supporting and inhibiting factors in developing the Matansala BUMDes. This study uses a qualitative descriptive method with a field study approach. Data collection techniques are carried out through observation, in-depth interviews, and documentation of informants consisting of the village government, BUMDes administrators, and members. The results of the study indicate that the BUMDes development strategy in Matansala Village is carried out through strengthening and managing several main business units, namely savings and loan units, tourism units based on mangrove tourism potential, and food security units in the form of laying hen businesses. The development of these business units contributes to increasing PADes while opening employment opportunities and increasing the income of the village community.